2001
DOI: 10.1111/j.1469-8749.2001.tb00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three ankle‐foot orthosis configurations for children with spastic hemiplegia

Abstract: The purpose of this study was to examine the effectiveness of the hinged ankle-foot orthosis (HAFO), posterior leaf spring (PLS), and solid ankle-foot orthosis (SAFO), in preventing contracture, improving efficiency of gait, and enhancing performance of functional motor skills in 30 children (21 male, 9 female; mean age 9 years 4 months; age range 4 to 18 years,) with spastic hemiplegia. Following a 3-month baseline period of no ankle-foot orthosis (AFO) use, each AFO was worn for 3 months after which ankle ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
99
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(115 citation statements)
references
References 21 publications
13
99
1
2
Order By: Relevance
“…This is in fact still true. As we reported, Ferdjallah et al (2003) demonstrated a difference in GMFM goal total scores between AFO and barefoot assessments in a very small sample of 5 children with spastic diplegia, while in a much larger sample of 30 children with hemiplegia, Buckon and colleagues 4 found no significant difference in GMFM goal total scores (Standing, and Walking, Running, Jumping) between the different AFOs or between use of AFOs and barefoot function. The fact that Maltais and colleagues found no significant difference between AFOs and shoes compared with shoes alone further highlights the need for additional study.…”
mentioning
confidence: 68%
“…This is in fact still true. As we reported, Ferdjallah et al (2003) demonstrated a difference in GMFM goal total scores between AFO and barefoot assessments in a very small sample of 5 children with spastic diplegia, while in a much larger sample of 30 children with hemiplegia, Buckon and colleagues 4 found no significant difference in GMFM goal total scores (Standing, and Walking, Running, Jumping) between the different AFOs or between use of AFOs and barefoot function. The fact that Maltais and colleagues found no significant difference between AFOs and shoes compared with shoes alone further highlights the need for additional study.…”
mentioning
confidence: 68%
“…ankle-foot orthosis), a wybór najodpowiedniejszej uzależniony jest od wieku dziecka, nasilenia przykurczy mięśniowych, jak i od stopnia dysfunkcji stawów i towarzyszących zniekształ-ceń stóp. Doniesienia naukowe oparte na nielicznych grupach chorych z mpd, dotyczące używania przez nich AFO, wskazują na korzyści płynące z ich stosowania w aspekcie biomechanicznym (na podstawie analizy trójprzestrzennej chodu), energetycznym (ocenionym za pomocą spirometrii i kalorymetrii), a przede wszystkim funkcjonalnym (wyrażo-nym poprawą wzorca chodu i postawy) [35][36][37][38][39][40][41][42].…”
Section: Ortezy Stawu Skokowegounclassified
“…W opinii Buckona i in. [40] zjawisko to świadczyć może o mniejszym zmęczeniu chorego dziecka, które towarzyszy chodzeniu w tym typie zaopatrzenia. Stosowanie AFO, ich zdaniem, poprawia również koordynację ruchową oraz obciążanie kończyn dolnych potwierdzone lepszymi wynikami w skali GMFM.…”
Section: Orthoses Of the Ankle Jointunclassified
See 2 more Smart Citations